Trains! - "Goodman, Susan E. " (New York; Random House, 2012)
Introduces the history of trains, from the nineteenth-century steam locomotives that bridged the American East and West to the Japanese "pusher" commuter trains and the Scottish train used as the Hogwarts Express in the "Harry Potter" films
Keywords: Railroad trains